Chemical components of deteriorated pine wood of beams of the Mitra building in Morelia, Mexico - Carrillo Gómez, Mayra Irery; Raya Gonzales, David; Ávila-Calderón, Luz Elena A. (Instituto de Ecología, A.C., 2023)
An analysis was carried out to determine the main chemical components of the wood of three pieces of pine beams from the archive area of the historic building known as La Mitra, in the city of Morelia, in Michoacán, Mexico. This analysis is complementary to one previously carried out, by means of ultrasound and for the purpose of conservation and restoration of historical structures. The beams that were analyzed here are part of the group that was studied in that first phase, randomly selected from a group of 40 and with dimensions of 25 cm × 17 cm × 60 cm. Sapwood and heartwood samples were taken in two different sections (decayed and healthy embedment area). For each beam, pH, ashes, ash analysis, extractable substances, holocellulose and lignin values were determined. The results found were: pH from 3.20 to 4.67, ashes 0.25% to 1.36%, with a higher concentration of oxygen (3.36% to 6.64%), calcium (1.80% to 3.46%), carbon (1.18% to 3.45%), potassium (0.20% to 0.84%), aluminum (0.17% to 0.31%), silicon (0.15% to 0.59%), and magnesium (0.15% to 0.56%); solubility in soda (9.83% to 27.78%), total extractables, in the sequential extraction, the highest solubility was obtained with acetone, (2.92% to 6.96%), followed by hot water (0.25% to 7.49%), methanol ( 2.03% to 6.22%) and cyclohexane (0.98% to 2.66%); holocellulose (68.22% to 84.01%) and lignin (24.19% to 31.83%). The pH, solubility in soda, holocellulose and lignin presented a statistically significant variation (P < 0.05) between sapwood and heartwood in healthy and deteriorated areas.